Exploring the Scalability of 5G-Enabled E-Learning Platforms in Rural Areas - Apriyanto Apriyanto; Ahmed Hossam; Yara Abed; Reddy Anggara (Yayasan Adra Karima Hubbi, 2024)
Background. The rise of 5G technology offers the potential to revolutionize e-learning, particularly in rural areas where access to high-quality educational resources has historically been limited. Despite the promise of improved connectivity, the scalability and impact of 5G-enabled e-learning platforms in these regions remain underexplored. Purpose. This study aims to assess the feasibility and scalability of implementing 5G-enabled e-learning platforms in rural areas and to evaluate their effectiveness in enhancing educational access and outcomes. Method. The research employs a mixed-method approach, combining quantitative analysis of internet connectivity, user engagement, and learning outcomes with qualitative interviews from educators and students. Data was collected from five rural regions across three countries where 5G infrastructure was recently introduced. The study measured improvements in e-learning adoption rates, student engagement, and academic performance over a 12-month period. Results. Results indicate that 5G-enabled e-learning platforms significantly improved both access to education and student engagement, with a 30% increase in platform adoption and a 25% improvement in student performance. Educators also reported more dynamic and interactive learning experiences. However, challenges related to infrastructure costs and digital literacy were noted, which could limit scalability in certain regions. Conclusion. In conclusion, the study demonstrates the potential of 5G technology to scale e-learning platforms in rural areas, improving educational access and outcomes. Nonetheless, addressing challenges such as infrastructure costs and digital literacy is critical for ensuring long-term scalability and success.